Tobacco smoking-associated genome-wide DNA methylation changes in the EPIC study. (May 2016) - Ambatipudi, Srikant; Cuenin, Cyrille; Hernandez-Vargas, Hector; Ghantous, Akram; Le Calvez-Kelm, Florence; Kaaks, Rudolf; Barrdahl, Myrto; Boeing, Heiner; Aleksandrova, Krasimira; Trichopoulou, Antonia; Lagiou, Pagona; Naska, Androniki; et al.
Aim : Epigenetic changes may occur in response to environmental stressors, and an altered epigenome pattern may represent a stable signature of environmental exposure.Materials & methods: Here, we examined the potential of DNA methylation changes in 910 prediagnostic peripheral blood samples as a marker of exposure to tobacco smoke in a large multinational cohort.Results : We identified 748 CpG sites that were differentially methylated between smokers and nonsmokers, among which we identified novel regionally clustered CpGs associated with active smoking. Importantly, we found a marked reversibility of methylation changes after smoking cessation, although specific genes remained differentially methylated up to 22 years after cessation.Conclusion : Our study has comprehensively cataloged the smoking-associated DNA methylation alterations and showed that these alterations are reversible after smoking cessation.